La mise en scène de la Lorraine au cinéma - Delphine Le Nozach; Violaine Appel (Communication)
This study is the result of research that examines depictions of France’s Grand Est administrative region in French fictional film. The themes of these films coincide with the communicational challenges facing public stakeholders—particularly the need to establish the new region’s identity while continuing to promote the specificities and assets of the Grand Est’s four constitutive regions (Alsace, Champagne, Ardenne, and Lorraine). The authors look at portrayals of Lorraine by local filmmakers. By studying their films and decoding their discourse, the authors reveal how Lorraine’s specific characteristics as a region are presented in film and identify a typology of three markers of regionality in film: society and culture, history, and memory.